2010
DOI: 10.1111/j.1525-1470.2010.01195.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Symptoms and Health-Related Quality of Life in Children and Adolescents with Psoriasis

Abstract: Information about the relationship between psoriasis and psychiatric morbidity and quality of life in children and adolescents is limited. We aimed to examine the symptoms of depression and anxiety and health-related quality of life levels in children and adolescents with psoriasis. Forty-eight outpatients with psoriasis aged 8 to 18 years are included in this study. Child Depression Inventory (CDI), State-Trait Anxiety Inventories for Children (STAI-C) and Pediatric Quality of Life Inventory Parent and Child … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
48
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 18 publications
(23 reference statements)
7
48
1
2
Order By: Relevance
“…These findings are similar to those of previous studies undertaken in other countries using various setups and sample sizes [23][24][25]. The effect on QoL of embarrassment and self-consciousness resulting from skin infection was also in line with other studies performed in central Saudi Arabia, in which the location of lesions caused by skin infection created a major psychological impairment in individual identity development [26,27]. Furthermore, the messiness and time-constraints imposed by the topical application of treatments for skin infection caused discomfort and annoyance [28].…”
Section: Discussionsupporting
confidence: 82%
“…These findings are similar to those of previous studies undertaken in other countries using various setups and sample sizes [23][24][25]. The effect on QoL of embarrassment and self-consciousness resulting from skin infection was also in line with other studies performed in central Saudi Arabia, in which the location of lesions caused by skin infection created a major psychological impairment in individual identity development [26,27]. Furthermore, the messiness and time-constraints imposed by the topical application of treatments for skin infection caused discomfort and annoyance [28].…”
Section: Discussionsupporting
confidence: 82%
“…54, 55 A recent prospective cohort study of 892 affected adult women found that increased adiposity preceded the occurrence of new onset psoriasis 21 ; we are currently addressing if increased adiposity precedes psoriasis onset in children.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important since depressive episodes at a young age increase the risk of subsequent recurrences and long-term psychiatric disorders [20] . Bilgic et al [21] performed a casecontrol study of 48 psoriatic patients and healthy controls aged 8-18 years and found no differences in depression and anxiety in the adolescent group (13-18 years old). This unexpected finding may be explained by a small sample size (n = 26) in combination with the fact that patients had only mild psoriasis (average Psoriasis Area and Severity Index, PASI, of 9.75 ± 10.52).…”
Section: Hrql In Adolescents With Chronic Illness and Psoriasismentioning
confidence: 99%